2016
DOI: 10.1016/j.yfrne.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo visualization of aromatase in animals and humans

Abstract: Aromatase catalyzes the last and obligatory step in the biosynthesis of estrogens across species. In vivo visualization of aromatase can be performed using positron emission tomography (PET) with radiolabeled aromatase inhibitors such as [11C]vorozole. PET studies in rats, monkeys and healthy human subjects demonstrate widespread but heterogeneous aromatase availability in brain and body, which appears to be regulated in a species, sex and region-specific manner. Thus, aromatase availability is high in brain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 76 publications
1
23
0
1
Order By: Relevance
“…Interestingly, E2 treatment has been shown to improve renal function in these animals [28]. However, interspecies differences in aromatase availability complicate any extrapolation of data derived from rodent experiments to human populations [29].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, E2 treatment has been shown to improve renal function in these animals [28]. However, interspecies differences in aromatase availability complicate any extrapolation of data derived from rodent experiments to human populations [29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was revealed that the presence of fadrozole, or possibly another aromatase inhibitor, is crucial for the observed effect of testosterone on induced pluripotent stem cell-derived human neurons, indicating that these female neurons produce aromatase and are able to facilitate the conversion of testosterone to estradiol in vitro. The presence of aromatase activity here may be unsurprising, as the protective properties of aromatase have been described, though not in the process of MS, 32,44e46 and various studies have found ubiquitous aromatase expression within both the human brain 38 and cultured murine spinal motor neurons. 37 Furthermore, though estrogens are generally considered to confer neuroprotection, 22,23 our testosterone-only treatment groups both in vivo and in vitro displayed a disease course and cell death ratio nearly identical to that of control.…”
Section: Discussionmentioning
confidence: 83%
“…In our models, testosterone administered to female mice or applied to female-derived neurons is likely to be at least partly converted into estradiol due to endogenous or neuronal production of aromatase. 37,38 Our studies employ the aromatase inhibitor fadrozole to prevent this. Hence, in the context of the EAE and in vitro neuronal experiments, T þ FAD treatments provide a pure androgenic effect and T treatments one of mixed estradiol/ testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Цей ферментний комплекс міститься в ендоплазматичному ретикулумі різних клітин, присутніх в яєчниках, плаценті, молочних залозах, матці, яєчках, мозку, жировій тканині тощо. Таким чином, у цих органах може відбуватися утворення естрогенів de novo або із транспортованих до них з інших тканин і депонованих там андрогенів (Biegon, 2016;Chan et al, 2016). Особливий інтерес у медицині викликає інтратуморальна ароматаза, зокрема, молочної залози.…”
Section: національний фармацевтичний університет харків українаunclassified